Substitution between immigrant and native farmworkers in the United States: Does legal status matter? - Xuan Wei; Gulcan Onel; Zhengfei Guan; Fritz M. Roka (IZA Journal of Development and Migration, 2019)
The policy debate surrounding the employment of immigrant workers in U.S. agriculture centers around the extent to which immigrant farmworkers adversely affect the economic opportunities of native farmworkers. To help answer this question, we propose a three-layer nested constant elasticity of substitution (CES) framework to investigate the substitutability among heterogeneous farmworker groups based on age, skill, and legal status utilizing National Agricultural Workers Survey (NAWS) data from 1989 through 2012. We use farmwork experience and type of task performed as alternative proxies for skill to disentangle the substitution effect between U.S. citizens, authorized immigrants, and unauthorized immigrant farmworkers. Results show that substitutability between the three legal status groups is small; neither authorized nor unauthorized immigrant farmworkers have a significant impact on the employment of native farmworkers.
Keywords: J20; J43; J61; 330; elasticity of substitution; immigration; legal status; agricultural labor; nested CES framework